KONSEP FITRAH DALAM PENDIDIKAN ISLAM PERSPEKTIF AL-QUR’AN DAN HADIST - Eko Nursalim; Iskandar (CV. Adiba Aisha Amira, 2021)
The concept of the nature of Islamic education in the perspective of the Koran and Hadith from the literature review that was carried out, there were several findings in the research including; First, etymologically, Fitrah means al-khilqah (instinct, nature) and al-thabī'ah (nature, character, character) which Allah swt created in humans. Fitrah is also taken from the word al-fathr which means shaq (split). From this meaning, other meanings are born, including creator or event. Second, all human nature in the form of the potential for piety, apart from trying to grow and develop, must and need to be educated and directed. Because the influence of parents (representing the environment in the form of association, reading, education, and so on) can affect humans to be bad, evil and so on. Third, if the child has a basic nature that is seen as an evil trait, educational efforts are to educate, direct and focus on eliminating and replacing or at least reducing the elements of the crime. Fourth, humans are blessed with two extraordinary potentials, namely reason ('aql) and free will (nafs). It turns out that these two potentials can be the cause of an advantage that is difficult to imagine, but at the same time can be a very fatal weakness as well